2018
DOI: 10.1080/15384101.2018.1496741
|View full text |Cite
|
Sign up to set email alerts
|

The long coding RNA AFAP1-AS1 promotes tumor cell growth and invasion in pancreatic cancer through upregulating the IGF1R oncogene via sequestration of miR-133a

Abstract: Long non-coding RNAs (lncRNAs) have been shown to play a significant role in the progression of many cancers, including pancreatic cancer (PC). However, the biological function and regulatory mechanisms of lncRNAs in PC remains largely unclear. The aim of this study was to identify and evaluate the potential functions of lncRNAs in PC and reveal the underlying mechanisms of their effects. Screening of published microarray data (GEO accession Nos. GSE16515 and GSE32688), revealed lncRNA AFAP1-AS1 to be one of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…LncRNAs, a kind of non-coding RNAs with more than 200 nt in length, are reported to play roles in a variety of human cancers, including PC [3][4][5][6]. For example, HOT-TIP, MALAT1 and MEG3 are regarded as important regulators of tumor progression [7].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs, a kind of non-coding RNAs with more than 200 nt in length, are reported to play roles in a variety of human cancers, including PC [3][4][5][6]. For example, HOT-TIP, MALAT1 and MEG3 are regarded as important regulators of tumor progression [7].…”
Section: Introductionmentioning
confidence: 99%
“…The knockdown of AFAP1-AS1 was validated to inhibit GC cell proliferation migration and AFAP1-AS1, also known as AFAP1-AS and AFAP1AS, is an antisense lncRNA 6810 bp in length located at the chromosome Chr4p16.1 [29]. AFAP1-AS1 has been reported to be aberrantly expressed and is able to function as a regulator of tumorigenesis in many tumors, including breast cancer, pancreatic cancer, non-small cell lung cancer, and colorectal cancer [19,20,22,30]. Guo et al [31] identified that AFAP1-AS1 was upregulated in GC cells and regulated GC cell proliferation and apoptosis via the PTEN/p-AKT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies have demonstrated that lncRNAs regulated gene expression through functioning as microRNA (miRNA) sponge or competing endogenous RNA (ceRNA) and play significant regulatory roles in tumor biology via various mechanisms associating with the aggressive development of cancer, including cell proliferation, differentiation, apoptosis, invasion, metabolism, developmental timing, and immune responses [16][17][18]. Recent studies have shown that lncRNA AFAP1-AS1 functions as a ceRNA in pancreatic cancer, breast cancer, lung cancer, and colorectal cancer [19][20][21][22]. However, the detailed function and mechanism of AFAP1-AS1 in the pathogenesis of GC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-133a could not only suppress cell proliferation, induce cell cycle arrest at G0/G1 stage and accelerate cell apoptosis, but also inhibit cell migration and invasion in vivo and in vitro via targeting IGF-1R and negatively regulating downstream AKT and ERK signal pathway [36][37][38]. In PC, AFAP1-AS1 was reported to induce IGF1R transcription and activate the AKT/ERK pathways to promote EMT and cell metasis by sponging miR-133a [39]. Downregulation of miR-133a-3p functioned as a supportive factor in bone metastasis of prostate cancer (PCa) possibly by targeting EGFR, FGFR1, IGF1R and MET, and inactivating PI3K/AKT signaling pathway [40].…”
Section: Mir-133a In Cell Migration and Invasionmentioning
confidence: 99%